2000
DOI: 10.1086/303040
|View full text |Cite
|
Sign up to set email alerts
|

Human mtDNA Haplogroups Associated with High or Reduced Spermatozoa Motility

Abstract: A variety of mtDNA mutations responsible for human diseases have been associated with molecular defects in the OXPHOS system. It has been proposed that mtDNA genetic alterations can also be responsible for sperm dysfunction. In addition, it was suggested that if sperm dysfunction is the main phenotypic consequence, these mutations could be fixed as stable mtDNA variants, because mtDNA is maternally inherited. To test this possibility, we have performed an extensive analysis of the distribution of mtDNA haplogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
323
3
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(353 citation statements)
references
References 44 publications
13
323
3
9
Order By: Relevance
“…We should pay attention to the probability that many different polymorphisms may militate against mitochondrial function together vs. single base differences. Ruiz-Pesini et al 6 demonstrated the existence of variable complex IV-specific and cytochrome c oxidase activities between haplotypes H and T. Variable complex I-specific activities were included in our investigation perhaps due to different mtDNA haplogroup polymorphisms.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We should pay attention to the probability that many different polymorphisms may militate against mitochondrial function together vs. single base differences. Ruiz-Pesini et al 6 demonstrated the existence of variable complex IV-specific and cytochrome c oxidase activities between haplotypes H and T. Variable complex I-specific activities were included in our investigation perhaps due to different mtDNA haplogroup polymorphisms.…”
Section: Discussionmentioning
confidence: 65%
“…In the study by Ruiz-Pesini et al, 6 mtDNA haplotype H was found to be underrepresented and haplotype T was overrepresented in men with asthenozoospermic ejaculates. Furthermore, significant differences in OXPHOS component activity were found between different haplotypes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Among Europeans, 95% of the population belongs to 1 of 9 haplogroups: H, I, J, K, T, U, V, W, or X. Given the lines of evidence that describe the contribution of mtDNA to cellular physiology, as well as its critical importance for energy production, a number of studies have investigated the association between mtDNA haplogroups and multifactorial diseases (22)(23)(24)(25)(26)(27)(28), mitochondrial diseases (29,30), and aging (31)(32)(33).…”
mentioning
confidence: 99%